A methodological combined framework for roadmapping biosensor research: a fault tree analysis approach within a strategic technology evaluation frame. (March 2014) - Siontorou, Christina G.; Batzias, Fragiskos A.
Abstract Biosensor technology began in the 1960s to revolutionize instrumentation and measurement. Despite the glucose sensor market success that revolutionized medical diagnostics, and artificial pancreas promise currently the approval stage, the industry is reluctant to capitalize on other relevant university-produced knowledge and innovation. On the other hand, the scientific literature is extensive and persisting, while the number of university-hosted biosensor groups is growing. Considering the limited marketability of biosensors compared to the available research output, the biosensor field has been used by the present authors as a suitable paradigm for developing a methodological combined framework for "roadmapping" university research output in this discipline. This framework adopts the basic principles of the Analytic Hierarchy Process (AHP), replacing the lower level of technology alternatives with internal barriers (drawbacks, limitations, disadvantages), modeled through fault tree analysis (FTA) relying on fuzzy reasoning to count for uncertainty. The proposed methodology is validated retrospectively using ion selective field effect transistor (ISFET) – based biosensors as a case example, and then implemented prospectively membrane biosensors, putting an emphasis on the manufacturability issues. The analysis performed the trajectory of membrane platforms differently than the available market roadmaps that, considering the vast industrial experience in tailoring and handling crystallic forms, suggest the technology path of biomimetic and synthetic materials. The results presented herein indicate that future trajectories lie along with nanotechnology, and especially nanofabrication and nano-bioinformatics, and focused, more on the science-path, that is, on controlling the natural process of self-assembly and the thermodynamics of bioelement-lipid interaction. This retained the nature-derived sensitivity of the biosensor platform, pointing out the differences between the scope of academic research and the market viewpoint.